Fabrication of recyclable nucleating agent and its effect on crystallization, gas barrier, thermal, and mechanical performance of Poly(l-lactide) - Liu, Ji-Hong; Huang, Ming-Lu; Tao, Jun-Ru; Weng, Yun-Xuan; Wang, Ming (Polymer (Guilford), 2021)
Herein, a recyclable nucleating agent for poly(l-lactide) (PLLA) was fabricated via taking advantage of grafting biodegradable poly(3-hydroxybutyrate)-diol onto the surface of magnetic nanoparticles (ferroferric oxide, Fe3O4). Its effectiveness in improving crystallinity, gas barriers, thermal, and mechanical performance of PLLA are investigated. Core-shell structure, which is the combination of PHB-diol (shell) and magnetic nanoparticle (core), are detected by means of transmission electron microscope. Differential scanning calorimeter results suggest Fe3O4@SiO2-PHB (MM) nanoparticles exert great potential in accelerating the crystallization rate. Besides, with the increment of crystallinity for PLLA matrix, oxygen permeability and water vapor permeability are reduced, while thermal stability and mechanical property increases. Most importantly, this magnetic nucleating agent can be recollected and re-manufactured into new batch of PLLA composites without losing the nucleation efficiency, which successfully keep consistent with recyclable and highly-efficient aspiration. A recyclable nucleating agent for poly(l-lactide) (PLLA) was fabricated via taking advantage of grafting biodegradable poly(3-hydroxybutyrate)-diol onto the surface of ferroferric oxide nanoparticles to improve crystallinity, gas barriers, thermal, and mechanical performance of PLLA. [Display omitted] •Recyclable magnetic particles was fabricated for improving PLLA crystallization.•The PLLA crystallinity increased to 37.9% via adding 10 wt% the particles.•Water vapor and oxygen permeability decreased in PLLA with the particles.•The particles could be easily recycled and maintained high nucleating efficiency.